Medidas de trabalhabilidade em pastas geopoliméricas de metacaulim e sua correlação com propriedades e características reológicas - Gasperi, Jessica de (2021)
Geopolymers are currently considered as alternative binder more sustainable when comparted to traditional Portland cement (PC), as well as better mechanical performance and extended service life, if these materials are produced correctly. Among the different barriers that hinder the large-scale inclusion of geopolymers in the construction industry, there is the absence of standards procedures aimed at their characterization. In PC-based concretes, the main properties that specifically define criteria for its execution and service are the mechanical strength (measured in a hardened state) and workability (fresh rheological property easily measured through simple, low-cost and standardized tests). In geopolymers, there is a scarcity of studies that discuss complex rheological properties and the absence of simpler methods than can be associated with rheometry to understand their behavior in the fresh state. This study evaluated the workability of geopolymeric pastes, through oscillatory rheometry with a parallel plate system and also analyzed the applicability of tests commonly adopted in cP, including well-established test methodologies, such as mini-slump and Marsh conel. Furthermore, the setting time was also assessed using the Vicat test, isothermal calorimetry, as well as compression strength. Different systems were produced from a single precursor (metakaolin: MK), different alkaline activator types (Na+ or K+), activation concentrations (15 and 20% M2O), and water/binder ratio (w/b: 0.70, 0.75 and 0.80). Simple and standardized tests were applicable to geopolymeric pastes with a spread greater than 70 mm and contributed to the understanding of the rheological behavior of the studied systems, when associated with rheometry. The type of alkaline cation (K+/Na+) was the factor with the greatest impact on the rheology, followed by the concentration (M2O) and lastly the w/b ratio. Systems produced from potassium showed greater fluidity (lower yield stress and consequently greater spread in the mini-slump test), as well as a higher elastic limit and lasted longer in a fresh state when compared to sodium-based systems. Sodium systems showed a faster fluid/solid transition, especially when activated with a lower Na2O concentration (15%), with greater stiffness (quantified through the sotarge moduli, G’) in the initial instants but with lower compression strength at 7 days when compared to systems with 20% Na2O.